2006
DOI: 10.1292/jvms.68.9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Parathyroid Hormone-Related Protein (PTHrP) mRNA in Mammary Gland of Periparturient Cows

Abstract: ABSTRACT. The expression of parathyroid hormone-related protein (PTHrP) mRNA was examined in mammary gland with or without lactation, and during periparturient period in a Holstein cow and a Jersey cow. In the lactating mammary gland, PTHrP was detected in alveolar epithelial cells and the lumen by immunohistochemical analysis. The relative expression levels of PTHrP mRNA in mammary gland from lactating cows were significantly higher than those from non-lactating cows (P<0.05). During periparturient period, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In milk goat, PTHrP was found to be highly expressed in the mammary gland (Yang et al, 2010). Past studies in cow showed that PTHrP was expressed in the mammary gland during late pregnancy and increased subsequently with lactation, suggesting that PTHrP is involved in regulating local Ca homeostasis (Wojcik et al, 1998;Onda et al, 2006b). The physiological function of a protein may indicate its tissue distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In milk goat, PTHrP was found to be highly expressed in the mammary gland (Yang et al, 2010). Past studies in cow showed that PTHrP was expressed in the mammary gland during late pregnancy and increased subsequently with lactation, suggesting that PTHrP is involved in regulating local Ca homeostasis (Wojcik et al, 1998;Onda et al, 2006b). The physiological function of a protein may indicate its tissue distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies have shown that PTHrP is produced not only in neoplastic tissues but also by many healthy human and animal tissues: thyroid gland, parathyroid gland, pituitary gland, salivary gland, urinary bladder, kidney, mammary gland, testis, epididymis, cartilage, osteoblasts, vascular smooth muscle cells [2,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. PTHrP is a very conservative peptide.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of parathyroid hormone-related protein (PTHrP) mRNA in the mammary gland was reported to increase dramatically at the onset of the lactation in rats and cows [12,20]. On the immunohistochemical findings, PTHrP was detected in the lactating mammary gland, especially in epithelial cells and in the lumen, suggesting that mammary PTHrP regulates Ca uptake and/or release in the mammary gland [12,13].…”
mentioning
confidence: 99%